THE ARCHITECTURE OF THE UNCANNY: A COMPARATIVE ANALYSIS OF FANTASTIC ELEMENTS IN E.T.A. HOFFMANN’S DER SANDMANN AND DER NUSSKNACKER UND DER MAUSEKÖNIG - Shahriyorov Otajon; Rustamov Orifjon (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the dual nature of the "fantastic" in the works of E.T.A.  Hoffmann,  specifically  examining  the  transition  between  the  psychological horror of The Sandman and the whimsical, yet eerie, world of The Nutcracker and the Mouse King. By analyzing Hoffmann’s "Serapiontic Principle"—the idea that the artist must see the internal vision clearly before translating it to reality—this paper argues that Hoffmann’s use of the fantastic is not merely escapism but a sophisticated critique of Enlightenment rationalism.